2002
DOI: 10.1152/ajpcell.00473.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apical Cl/OH exchange activity in Caco-2 cells by phorbol esters is mediated by PKCε

Abstract: The present studies were undertaken to examine the possible regulation of apical membrane Cl−/OH− exchanger in Caco-2 cells by protein kinase C (PKC). The effect of the phorbol ester phorbol 12-myristate 13-acetate (PMA), an in vitro PKC agonist, on OH−gradient-driven 4,4′-diisothiocyanostilbene-2,2′-disulfonic acid (DIDS)-sensitive 36Cl uptake in Caco-2 cells was assessed. The results demonstrated that PMA decreased apical Cl−/OH− exchanger activity via phosphatidylinositol 3-kinase (PI3-kinase)-mediated acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Our data showed that the effects of LPA on Cl Ϫ /OH Ϫ exchange activity were blocked in the presence of PI3 kinase and Akt inhibitors, indicating the involvement of PI3 kinaseAkt pathway. The involvement of PI3 kinase-dependent pathway is in agreement with other previous studies from our laboratory that have shown the involvement of PI3 kinase in the regulation of Cl Ϫ /OH Ϫ exchange activity by Lactobacillus acidophilus, taurodeoxycholic acid, and PMA (1,8,33). Furthermore, PI3 kinase has been shown to be involved in medi- Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data showed that the effects of LPA on Cl Ϫ /OH Ϫ exchange activity were blocked in the presence of PI3 kinase and Akt inhibitors, indicating the involvement of PI3 kinaseAkt pathway. The involvement of PI3 kinase-dependent pathway is in agreement with other previous studies from our laboratory that have shown the involvement of PI3 kinase in the regulation of Cl Ϫ /OH Ϫ exchange activity by Lactobacillus acidophilus, taurodeoxycholic acid, and PMA (1,8,33). Furthermore, PI3 kinase has been shown to be involved in medi- Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Cl Ϫ /OH Ϫ exchangers or anion exchangers are known to play a pivotal role in the vectorial transport of Cl Ϫ across the plasma membrane of polarized epithelial cells. Previously, we have shown that apical Cl Ϫ / OH Ϫ exchange activity is inhibited by various inflammatory mediators, such as nitric oxide, serotonin, and phorbol esters, and also by infection with enteropathogenic Escherichia coli in Caco-2 cells and is stimulated by probiotic bacterium, Lactobacillus acidophilus (8,14,(33)(34)(35). In the present studies, our data for the first time demonstrate that LPA significantly stimulates Cl Ϫ /OH Ϫ exchange activity in Caco-2 cells via activation of PI3 kinase/Akt pathways, suggesting that this effect of LPA could contribute to potential antidiarrheal effects of LPA.…”
Section: Discussionmentioning
confidence: 99%
“…Through a series of pharmacological experiments using a monolayer model, Yoo et al (2001) showed that PKC-⑀ may inhibit hypoxia-induced secretory responses in epithelial cells. This finding was later reproduced by Saksena et al (2002), who showed that EGF inhibited basolateral Cl Ϫ secretion through activation of PKC-⑀. Later studies suggested that PKC-⑀ has an inhibitory role in TNF-induced barrier dysfunction (Yoo et al, 2001).…”
Section: Pkc-␦mentioning
confidence: 67%
“…Chloride uptake experiments were performed essentially as described by Olsnes et al (37) with some modifications (38,39). Caco-2 cells were incubated with Dulbecco's modified Eagle's base media containing 20 mM Hepes/KOH, pH 8.5, for 30 min at room temperature.…”
Section: CLmentioning
confidence: 99%
“…The cells were then incubated with the uptake buffer for a 5-min period. This period was chosen because it falls within the linear range of Cl Ϫ uptake in this system (38,39). For 36 Cl Ϫ uptake studies, the uptake buffer was the mannitol buffer containing 1.4 Ci of 36 Cl Ϫ (2.9 mM) of hydrochloric acid (specific activity-17.12 mCi/g) Ϯ 0.3 mM DIDS.…”
Section: CLmentioning
confidence: 99%